Pelatihan Dan Branding Usaha Mikro Kecil Dan Menengah (UMKM) Wolamgrezz Melalui Media Digital E-Commerce - Dennis Aprilianti; Rafly Sandi Putra; Dhian Satria Yudha Kartika; Tiara Putri Marcela; Raffli Amirullah; Cindy Dyah (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2023)
Micro, Small and Medium Enterprises (MSME) are sectors that are influential in running the economy in the community. MSME are also expected to be able to contribute in creating employment opportunities for the surrounding community, so as to be able to reduce poverty in an area. The existence of the Wolamgrezz MSME in Carangwulung village actually has the potential to become a large MSME in the Wonosalam District and even the entire Jombang Regency, because these UMKM raise the region's superior crops. Therefore, Wolamgrezz MSME must be fully supported in running their business, so that the existing potential can run optimally and can become the leading MSME in Jombang Regency. However, in carrying out its business, Wolamgrezz has several problems that arise in the field, such as obstacles to product promotion through digital e-commerce media and product marketing only by word of mouth, so that consumers who know Wolamgrezz's MSME products are very limited and only within the scope of Carangwulung village. Therefore, the branding and marketing of UMKM Wolamgrezz products must be carried out immediately and intensified so that they can attract consumers widely so that product sales can increase and income will also increase, and this can also affect the opening of new job vacancies.